Prospective and randomised evaluation of the protease-modulating effect of oxidised regenerated cellulose/collagen matrix treatment in pressure sore ulcers - Kloeters, Oliver; Unglaub, Frank (International wound journal, 2016)
In chronic wounds, excess levels and activity of proteases such as elastase and plasmin have been detected. Oxidised regenerated cellulose/collagen matrix (ORC/collagen matrix) has been reported to ameliorate the wound microenvironment by binding and inactivating excess proteases in wound exudates. In this study, the levels and activity of elastase and plasmin in wound exudates of pressure sore ulcers were measured to determine the beneficial effect of ORC/collagen matrix treatment compared with control treatment with a foam dressing. A total of 33 patients with pressure sores were enrolled in the study and were followed up for 12 weeks after treatment. Ten control patients were treated with a foam hydropolymer dressing (TIELLE®, Systagenix), and the remaining 23 patients were treated with ORC/collagen matrix plus the foam dressing (TIELLE®, Systagenix) on top. Wound assessments were carried out over 12 weeks on a weekly basis, with dressing changes twice a week. Ulcers were photographed and wound exudates were collected on admission and at days 5, 14 and then every 14 days to provide a visual record of any changes in appearance of the ulcer and healing rate and for biochemical analysis of the wound. The levels and activity of elastase and plasmin were measured in wound exudates. Statistical analysis was performed using ANOVA and Bonferroni's post hoc test with P-values <0·05 considered to be significant. Compared with controls, ORC/collagen matrix-treated pressure sore wounds showed a significant faster healing rate, which positively correlated with a decreased activity of elastase and plasmin in wound exudates. No signs of infection or intolerance to the ORC/collagen matrix were observed.
Gesehen am 30.10.2019
First published: 23 May 2015